Integration of Local Wisdom in Sociology Learning to Strengthen Cultural Identity - Muhammad Nur; Muhammad Alkhafi Akhmad; Arisnawawi Arisnawawi; Andi Samsul Alam; Indriani Indriani (Journal of Indonesian Progressive Education, 2026)
This study examines the integration of local wisdom into sociology learning and its contribution to strengthening students’ cultural identity at SMA Negeri 2 Sinjai. The research was motivated by the growing influence of globalization, which has led to shifts in cultural values among younger generations, highlighting the need for educational strategies that preserve and reinforce cultural identity. A descriptive qualitative approach was employed, with data collected through observations, interviews, and documentation. The participants consisted of sociology teachers, students, the school principal, and community leaders selected through purposive sampling. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation techniques. The findings reveal that the integration of local wisdom in sociology learning is implemented by connecting learning materials with local cultural values, such as mutual cooperation, Bugis traditions, and the social norms of the Sinjai community. These values are incorporated through discussion-based learning, case studies, and environment-oriented assignments. Teachers facilitate this process by utilizing students’ experiences, real-life social situations, and local social phenomena, making the learning process more contextual and meaningful. The integration of local wisdom positively influences students by enhancing their understanding of local culture, fostering appreciation for social values, and strengthening pride in their regional cultural identity. Therefore, local wisdom-based sociology learning not only improves students’ academic comprehension but also contributes to character development and the reinforcement of cultural identity in the contemporary era.